The relationship between the implementation of the five pillars of Community-Led Total Sanitation (CLTS) and the incidence of stunting at Sei Bejangkar Community Health Center - Sylvana, Dhini; Husna, Fika Amaliza; Rahmadayani, Fanny; Djuang, Michelle Hendriani; Akbar, Khainir; Ibnu, Syahroni; Djohan, Djohan; Hutagalung, Tommy Rizky; Puspawani, Yeni; Napitu, Sabar Hamonangan Victorianus; Baeha, Ferdinando Motuho; Tarigan, Setia Budi (Buletin Kedokteran & Kesehatan Prima, 2025)
Researchers were interested in studying the impact of Community-based total sanitation on stunting in the service area of the Sei Bejangkar Health Center since the first survey indicated that 90 toddlers were stunted owing to the effects of inadequate sanitation. The study used a quantitative, cross-sectional methodology. This research was carried out near the Sei Bejangkar Health Center. All of the infants and toddlers in the puskesmas's operational region served as the study's population. Total sampling was used during the sampling process. Univariate, Bivariate, and Multivariate tests were utilized to analyze both main and secondary data in this study. Based on the data, it appears that there is no connection between the halt defecation movement and stunting in toddlers in the sei anchor health center's service area (P value of 0.529 or more than 0.05). Toddlers at the Sei Bejangkar Health Center are less likely to be stunted if open defecation is reduced. The p-value is 0.000, which means it's significantly larger than 0.05 (0.000 > 0.05).